PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DI KLINIK KECANTIKAN RUMAH CANTIK ALAMANDA KRIAN - APRILIANI, IKE (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
How do we look to others is considered most essential formost people. For body treatment, the health of the skin on the face and the body took the most attention. This one issue alone has ended up created a competitive climate to the skin beauty and aesthetic bussiness. One of those beauty clinics that focused on the customer service quality is Rumah Cantik Alamanda Krian. The variable being put into observation are tangible (X1), reliability (X2), assurance (X3), emphaty (X4), and responsiveness (X5) serve as independent variables while the customers’s loyalty defined as dependent variable (Y). This instrumen uses questionnaires as main instrument to get data from 178 respondents. This observation might be conclude that the independent variable altogether are making a partial and simultaneous affection towards the loyalty of the customers at Rumah Cantik Alamanda Krian. Keyword : Service Quality, Tangible, Reliability, Assurance, Emphaty, Responsiveness, Customer’s Loyalty